The Impact of Living Arrangements (In-Camp versus Out-of-Camp) on the Quality of Life : A Case Study of Syrian Refugees in Jordan - Obi, Chinedu Temple (World Bank, Washington, DC, 2021)
Refugee camps are believed to represent safe havens for forcibly displaced persons, but studies looking at refugees' quality of life in camps are few. This paper explores how Syrian refugees’ quality of life in camps in Jordan differs from that of Syrian refugees residing outside camps. Using data from the Syrian Refugee and Host Community Survey, the study measures life quality through indicators of subjective life experience and material living conditions. Data are analyzed using advanced statistical methods (difference-in-difference and propensity score matching) to control for selection bias that could skew estimates of causal effects. The results show that refugees living outside camps enjoy a higher quality of life than those living in camps. Out-of-camp refugees are less likely to live below the national abject poverty line or in overcrowded houses. They possess more household assets, are more satisfied with access to services, and report higher life satisfaction. Refugee camps appear to serve as safe havens for refugees who lack the capability to exit camps, and camps could be redundant for those who possess adequate capabilities and freedom to function in the urban and peri-urban areas.